2016
DOI: 10.1128/microbiolspec.vmbf-0009-2015
|View full text |Cite
|
Sign up to set email alerts
|

Type V Secretion Systems in Bacteria

Abstract: Type V secretion denotes a variety of secretion systems that cross the outer membrane in Gram-negative bacteria but that depend on the Sec machinery for transport through the inner membrane. They are possibly the simplest bacterial secretion systems, because they consist only of a single polypeptide chain (or two chains in the case of two-partner secretion). Their seemingly autonomous transport through the outer membrane has led to the term "autotransporters" for various subclasses of type V secretion. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 176 publications
1
35
0
Order By: Relevance
“…The observation that a disordered, negatively charged polypeptide can be secreted thus suggests that an electrochemical potential based on large, impermeable charged molecules may indeed be present across the bacterial OM and play a role in type V secretion. In addition, the process might also benefit from entropic effects due to the difference between the crowded periplasmic environment and the extracellular milieu (Fan et al, 2016); however, extracellular crowding agents have not been observed to affect AT secretion (Drobnak et al, 2015). …”
Section: Pathway Of Tpsa Proteins Across the Cell Envelopementioning
confidence: 99%
See 2 more Smart Citations
“…The observation that a disordered, negatively charged polypeptide can be secreted thus suggests that an electrochemical potential based on large, impermeable charged molecules may indeed be present across the bacterial OM and play a role in type V secretion. In addition, the process might also benefit from entropic effects due to the difference between the crowded periplasmic environment and the extracellular milieu (Fan et al, 2016); however, extracellular crowding agents have not been observed to affect AT secretion (Drobnak et al, 2015). …”
Section: Pathway Of Tpsa Proteins Across the Cell Envelopementioning
confidence: 99%
“…They are homotrimers whose passenger domains assemble into long, rather rigid stalks with a “head,” and harbor domains rich in β structure interspersed with helical coiled coils (reviewed in Fan et al, 2016). Each monomer contributes its four C-terminal β strands to the pore-forming transmembrane β barrel (Leo et al, 2012).…”
Section: Introduction: An Overview Of Type V Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ail is furthermore required for full virulence of Y. pestis and the delivery of pathogenicity factors into host cells (9)(10)(11)(12). The invasin subfamily comprises adhesins of the inverse autotransporter group also referred to as type Ve secretion system (13,14). InvA represents the prototype of the large bacterial invasin subfamily of adhesins (reviewed in (2,3,13)).…”
mentioning
confidence: 99%
“…Because these systems are detailed elsewhere in this special edition, we have focused our review on studies where spatial distribution appears to be important either to the biogenesis of the secretion system, or to its function. As highlighted in Figure 2, the architecture of these secretion nanomachines can differ from single component systems, to relatively simple systems composed of only 3 subunits, to multicomponent systems containing over 20 protein subunits and spanning all four compartments of the bacterial cell (Dalbey and Kuhn, 2012; Campos et al, 2013; Galán et al, 2014; Ho et al, 2014; Thomas et al, 2014; Trokter et al, 2014; van Ulsen et al, 2014; Zoued et al, 2014; Basler, 2015; Costa et al, 2015; Fan et al, 2016; Notti and Stebbins, 2016). …”
Section: Fluorescence-based Imaging Of Bacterial Secretion Systemsmentioning
confidence: 99%